The Value of Postsecondary Credentials in the Labor Market: An Experimental Study - Deming, David J.; Yuchtman, Noam; Abulafi, Amira; Goldin, Claudia; Katz, Lawrence F. (American Economic Review, 2016)
We study employers' perceptions of the value of postsecondary degrees using a field experiment. We randomly assign the sector and selectivity of institutions to fictitious resumes and apply to real vacancy postings for business and health jobs on a large online job board. We find that a business bachelor's degree from a for-profit online institution is 22 percent less likely to receive a callback than one from a nonselective public institution. In applications to health jobs, we find that for-profit credentials receive fewer callbacks unless the job requires an external quality indicator such as an occupational license. (JEL I23, I26, J24, J44, J63, M51)